Specifying Quantities in Software Models - Burgueño-Caballero, Lola; Mayerhofer, Tanja; Wimmer, Manuel; Vallecillo-Moreno, Antonio Jesús (My University, 2020)
Context: An essential requirement for the design and development of any engineering application that deals with real-world physical systems is the formal representation and processing of physical quantities, comprising both measurement uncertainty and units. Although solutions exist for several programming languages and simulation frameworks, this problem has not yet been fully solved for software models. Objective: This paper shows how both measurement uncertainty and units can be effectively incorporated into software models, becoming part of their basic type systems. Method: We introduce the main concepts and mechanisms needed for representing and handling physical quantities in software models. More precisely, we describe an extension of basic type Real, called Quantity, and a set of operations defined for the values of that type, together with a ready-to-use library of dimensions and units, which can be added to any modeling project. Results: We show how our approach permits modelers to safely represent and operate with physical quantities, statically ensuring type- and unit-safe assignments and operations, prior to any simulation of the system or implementation in any programming language. Conclusion: Our approach improves the expressiveness and type-safety of software models with respect to measurement uncertainty and units of physical quantities, and its effective use in modeling projects of physical systems.
Preprint aceptado para su publicación: Loli Burgueño, Tanja Mayerhofer, Manuel Wimmer, Antonio Vallecillo. "Specifying quantities in software models." Information and Software Technology, 113:82-97, 2019
Keywords: Incertidumbre (Teoría de la información); Ingeniería de sistemas; Model-based engineering; Modeling physical quantities; Measurement uncertainty